Multicenter Analysis of Genomically Targeted Single Patient Use Requests for Pediatric Neoplasms. Issue 34 (1st December 2021) - Sabnis, Himalee S.; Shulman, David S.; Mizukawa, Benjamin; Bouvier, Nancy; Zehir, Ahmet; Fangusaro, Jason; Fabrizio, Vanessa A.; Whitlow, Chanta; Winchester, Marilyn; Agresta, Laura; Turpin, Brian; Wechsler, Daniel S.; et al.
Abstract : PURPOSE: The US Food and Drug Administration–expanded access program (EAP) uses a single patient use (SPU) mechanism to provide patient access to investigational agents in situations where no satisfactory or comparable therapy is available. Genomic profiling of de novo and relapsed or refractory childhood cancer has led to increased identification of new drug targets in the last decade. The aim of this study is to examine the SPU experience for genomically targeted therapies in patients with pediatric cancer. PATIENTS AND METHODS: All genomically targeted therapeutic SPUs obtained over a 5-year period were evaluated at four large pediatric cancer programs. Data were collected on the type of neoplasm, agents requested, corresponding molecularly informed targets, and clinical outcomes. RESULTS: A total of 45 SPUs in 44 patients were identified. Requests were predominantly made for CNS and solid tumors (84.4%) compared with hematologic malignancies (15.6%). Lack of an available clinical trial was the main reason for SPU initiation (64.4%). The median time from US Food and Drug Administration submission to approval was 3 days (range, 0-12 days) and from Institutional Review Board submission to approval was 5 days (range, 0-50 days). Objective tumor response was seen in 39.5% (15 of 38) of all evaluable SPUs. Disease progression was the primary reason for discontinuation of drug (66.7%) followed by toxicity (13.3%). CONCLUSION: SPU requests remain an important mechanism for pediatric access to genomically targeted agents given the limited availability of targeted clinical trials for children with high-risk neoplasms. Furthermore, this subset of SPUs resulted in a substantial number of objective tumor responses. The development of a multi-institutional data registry of SPUs may enable systematic review of toxicity and clinical outcomes and provide evidence-based access to new drugs in rare pediatric cancers.